Obtención y caracterización de un bioplástico a partir de la semilla de aguacate_Aguaplast (2020)
In the present investigation, the production process of a bioplastic obtained from from isolated starch from Hass avocado seeds, with the aim of analyzing the effect of changes in the drying conditions of the starch production process and its use in different polymeric film formulations. The study was carried out in two phases. In the first phase, starch was isolated by the process wet milling and drying conditions and methods were evaluated. Furthermore, if analyzed the chemical structure of the isolated starch samples and compared them with a cassava starch commercial standard. In the second stage of the study, polymeric films were obtained from different formulations based on starch, with variation in the amount of glycerol and casein. I know evaluated a total of 4 formulations with variation of casein and compared with the film a cassava starch base with glycerin. It was concluded that films with a higher starch content become more viscous and a of its applications are films, instead the films with the highest casein content are can be considered for applications such as edible films with little environmental impact, buttons, leather, ivory, among others.